Does witnessing animal cruelty and being abused during childhood predict the initial age and recurrence of committing childhood animal cruelty? - Browne, John A. (International journal of offender therapy and comparative criminology, 2017)
The goal of the current study was to examine the association between demographic characteristics and childhood experiences on the respondents’ age of committing childhood animal cruelty and its recurrency. Using data collected from 257 male inmates at a Southern medium-security state prison, the current study seeks to replicate a study by Hensley, Tallichet, and Dutkiewicz. Results revealed that those respondents who were physically abused as children reported engaging in recurrent animal cruelty. The younger the age of respondent for first witnessing animal cruelty, the sooner his initiation to hurting and killing animals occurred. In addition, those who reported witnessing a parent commit acts of animal abuse reported that they committed animal abuse themselves at an older age, while those who witnessed a brother/sister commit animal abuse reported engaging in it at an earlier age. Therefore, physical abuse and witnessing primary socializers engage in animal abuse seem to be important in understanding the respondents’ age of onset and repeated childhood animal cruelty.